Digital Literacy, Proactive Personality, Pedagogical Competence, and Instructional Quality among Teachers in Indonesia - Damanik, Jafriansen; Widodo, Widodo; Taufik, Taufik; Sariyo, Harsono; T. Simorangkir, Sahat; S. Haratua, Chandra (Asian Journal of Interdisciplinary Research, 2026)
This study seeks to evaluate the impact of pedagogic competence on the relationship between digital literacy, proactive personality, and the quality of instructional delivery by teachers. The sample comprises 575 educators from Jakarta, West Java, and Banten in Indonesia. The data was gathered by a questionnaire employing a Likert Scale. The investigation employs Partial Least Squares-based Structural Equation Modeling. The study findings indicate that digital literacy, proactive personality, and pedagogical competence influence instructional quality; furthermore, digital literacy and proactive personality significantly impact teachers’ pedagogical competence. This study established a contextual validation of the influence of digital literacy and proactive personality on teachers’ instructional quality, mediated by pedagogical competence in the Indonesian context. It substantially contributes to the theoretical study of management, technology, and educational psychology and offers practical applications for educational implementation, particularly in improving the teachers’ instructional quality by promoting digital literacy and a proactive personality through the mediation of pedagogical competence. Therefore, this model warrants critical, in-depth discussion among researchers and practitioners before it is used as a reference, adapted, adopted, or modified to support their future work.